2013
DOI: 10.4103/0019-5413.118200
|View full text |Cite
|
Sign up to set email alerts
|

Results of titanium locking plate and stainless steel cerclage wire combination in femoral fractures

Abstract: Background:Some in vitro studies warn combining different metals in orthopedic surgery. The aim of this study is to determine the impact of combining titanium and stainless steel on bone healing and the clinical course of patients undergoing internal fixation of femoral fractures.Materials and Methods:69 patients with femoral fractures had polyaxial locking plate osteosynthesis. The locking plate was made of a titanium alloy. Two different cohorts were defined: (a) sole plating and (b) additional stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…25 However, numerous laboratory, animal, and human studies have shown that combination of dissimilar screws and plates did not accelerate the corrosion than the single-material constructions, indicating comparable clinical safety. 25,26 In the present case, combination of titanium and stainless steel implants did not show any negative effect on fixation stability or bone incorporation at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 46%
“…25 However, numerous laboratory, animal, and human studies have shown that combination of dissimilar screws and plates did not accelerate the corrosion than the single-material constructions, indicating comparable clinical safety. 25,26 In the present case, combination of titanium and stainless steel implants did not show any negative effect on fixation stability or bone incorporation at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 46%
“…We consider it salient to carry out long-term clinical and radiologic follow-up of the patient to determine this effect in our particular technique. 17 The clinical relevance of our technique is that it allows early mobilization and weight-bearing, allowing rapid rehabilitation and return to the previous functionality. Our patient shows good clinical results on the immediate postoperative period, 2 weeks, 1 month, and 8 months of follow-up, especially with complete resolution of thigh pain and no radiologic signs of development of new loosening of the endoprosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies such as that of El-Zayat and colleagues, show that there are no differences in bone healing or clinical results in patients with femoral fractures. We consider it salient to carry out long-term clinical and radiologic follow-up of the patient to determine this effect in our particular technique 17…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we advise surgeons to follow the current literature and evidence when treating a patient. There is available literature where authors have studied clinical effects of mixing titanium and stainless-steel implants invivo and have found no adverse effects (El-Zayat et al, 2013;Serhan et al, 2004;Koh et al, 2015;Høl et al, 2008. ).…”
Section: Discussionmentioning
confidence: 99%